Análise de perda de vida útil em transformadores isolados em óleo causada por sobrecorrente - Alves, Guilherme Bezerra (2018)
The oil transformer has its useful life drop when there is a temperature above the maximum elevation. Thus, first there is a study on the thermodynamics of the transformer, which includes the temperature limits, the winding temperature as a function of the overcurrent and the time required to reach a temperature that will lead to acceleration of the degradation of the insulation. The main effect of the loss of useful life is the deterioration of the insulation paper, which ends up determining the operating time of the equipment. One way to avoid this damage is by using vegetable oil as a substitute for the mineral. An overcurrent can be caused by an overload, a low power factor, excessive harmonics in the system, undervoltage or can be produced by a combination of defects. Overvoltages produce partial discharges that may lead to total loss of insulation; the high temperature of a short circuit has the same effect. To avoid such defects there must be an adequate protection system, periodic maintenance, installation of filters, correction of power factor and installation of a voltage regulator. This will ensure that the transformer has a longer life.